Electroanalysis overview: Addressing the green credentials in the use of electroanalytical sensors - Robert D. Crapnell; Craig E. Banks (Green Carbon)
Electrochemical methodologies provide a wide arsenal of options for analytical sensors, providing a high sensitivity, short analysis time, low-cost, possibility for miniaturization, and are readily portable solutions. One common theme within the literature is the use of the word “green”. The use of this terminology is intended to demonstrate the development of electroanalytical sensing platforms utilizing biodegradable and sustainable materials. In many cases, the claims of “green” electroanalytical platforms is questionable. This minireview looks to address the green credentials that are utilized in the pursuit of electroanalytical sensors, offering insights into future research opportunities.